Renin‐Angiotensin‐Aldosterone System Profiling in Horses Before and After Exercise - Todd Holbrook; Jorge Hernandez; Taralyn McCarrel; Guy Lester; Margaret Sleeper; Oliver Domenig; Darcy Adin (Journal of Veterinary Internal Medicine)
ABSTRACT Background The impact of exercise on the classical and alternative renin‐angiotensin‐aldosterone system (RAAS) pathways has not been studied in horses. Hypothesis We hypothesized that exercise would activate both RAAS pathways and that endurance exercise would cause more activation of the classical pathway compared to short‐duration, high‐intensity exercise in horses. Animals Twenty‐five horses (21 client‐owned and 4 research) were included in 4 exercise groups (10 Arabians, 50‐mile ride [A‐E]; 4 thoroughbreds, 1‐mile treadmill exercise [TB‐TM]; 5 thoroughbreds, 1–1/16th‐mile race [TB‐R]; and 6 quarter horses 330‐500‐yard race [QH‐R]). Methods Blood was collected before and after exercise. Equilibrium analysis was performed to measure serum RAAS metabolites and enzyme activities. The components of the RAAS pathways were compared before and after exercise. Post/pre‐exercise ratios for each variable were compared among exercise groups. Data were reported as median (first, third quartiles; pre vs. post) and p < 0.05 was considered significant. Results Exercise increased classical RAAS metabolites (pmol/L; angiotensin I, 2.5 [2.5, 2.5] vs. 8.2 [2.5, 19.0]; angiotensin II, 10.2 [6.0, 21.9] vs. 53.0 [37.4, 95.8]; aldosterone, 83.8 [53.4, 149.5] vs. 170.6 [112.2, 251.7]); alternative RAAS metabolites (pmol/L; angiotensin 1–7, 1.5 [1.5, 1.5] vs. 5.1 [1.5, 12.5]; angiotensin 1–5, 2.5 [2.5, 7.3] vs. 14.9 [9.0, 25.4]) and angiotensin‐converting enzyme‐2 activity (ng/mL; 16.6 [13.9, 20.4] vs. 25.2 [20.2, 33.0]; p < 0.001) for all horses. Angiotensin 1–7 ratios were higher for TB‐R compared with TB‐TM and A‐E (p < 0.001). Conclusions and Clinical Importance Both classical and alternative RAAS pathways increase after exercise in horses.